No Logos: Phenomenology, Animal Studies, and Logocentrism: Review of Louise Westling, The Logos of the Living World: Merleau-Ponty, Animals, and Language - Meighoo, Sean (Humanimalia, 2016)
Louise Westling, The Logos of the Living World: Merleau-Ponty, Animals, and Language. New York: Fordham University Press, 2014. 208 pp. 80.00 hb; 29.00 pb.